Pengaruh Upah Minimum, Nilai Tukar Petani, dan Inflasi Sektoral terhadap Kemiskinan di Pulau Jawa - Irma Ismawati; Syarwani Canon; Fitri Hadi Yulia Akib (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The phenomenon of poverty often occurs in every country, especially in developing countries. The level of poverty in a country depends on two main factors, namely the average level of national income and the width of the income distribution gap. Poverty cannot only be measured through income national per capita because per capita income calculates the average income of people in a country. The high level of per capita national income in a country, if the distribution of income is unequal then the level of poverty in that country cannot be avoided, and vice versa, no matter how equal the distribution of income in a country is, if the average level of national income is low, then poverty will also become more widespread. This research aims to determine the effect of minimum wages, farmer exchange rates, and inflation in the primary sector, secondary sector and tertiary sector on poverty on the island of Java. This research uses quantitative research methods using secondary data sourced from the Central Statistics Agency (BPS), using panel data analysis techniques. In this research, it was found that economic factors such as the Provincial Minimum Wage (UMP), Farmer Exchange Rate (NTP), and the inflation rate had a significant influence on the poverty level on the island of Java in the 2017-2022 period.